Comparison of Dynamic Visual Acuity in Spectacles Prescribed to 0.05D Versus 0.25D Steps: A Self-Control, Randomized Study - Zhixin Duan; Ningkai Tang; Yuexin Wang (Photonics, 2025)
The research aims to compare the dynamic visual acuity (DVA) in myopic adults wearing spectacles prescribed to 0.05D and 0.25D steps. This double-blind, randomized, self-control study included 40 myopic participants aged 18–40. The participants were randomly assigned to receive spectacles with one 0.05D step lens and the contralateral lens of 0.25D step. The monocular horizontal and vertical motion DVA at 20 and 40 degrees per second (dps) was measured. The DVA was compared between eyes with 0.25D and 0.05D step lenses and further analyzed by eye dominance and test sequence. The result demonstrated no significant difference in DVA between two eyes with 0.25D or 0.05D step lenses at 20 and 40 dps horizontal and vertical motion test (p > 0.05, respectively). When the eye with a 0.25D step lens was the dominant eye (p = 0.004) or measured secondly (p = 0.002), it outperformed the contralateral eye with a 0.05D step lens in the 40 dps horizontal motion test. In conclusion, the horizontal and vertical motion DVA of the eye with 0.05D step lens spectacles was comparable to that of contralateral eyes corrected with 0.25D step lens.